Evaluasi Risiko Postur Kerja Pegawai Administrasi Menggunakan Metode SNQ dan ROSA di CV. Rempah Sari - Muhammad Ilham Adelino; Susriyati; Muhammad Irwan (Universitas Putra Indonesia YPTK Padang, 2023)
Musculoskeletal Disorders (MSDs) is damage to the musculoskeletal system that accumulates and causes abnormalities due to repeated trauma, causing complaints of pain in the muscles. Ergonomics has an important role in preventing MSDs. Employee work activities at CV. Rempah Sari is an industrial company engaged in cinnamon bark. Workers feel complaints on the upper neck, lower neck, left shoulder, right shoulder, back, right arm, left arm, waist, hips and on the knee. The purpose of this study was to evaluate and analyze the risk level of the administrative department's work posture using the Standard Nordic Questionnaire (SNQ) and Rapid Office Strain Assessment (ROSA) methods. The results of this study using the SNQ method show that employees complain about the neck, shoulders, arms, back, waist, hips, buttocks, and need immediate repairs. The results of the ROSA calculation show that employees A, employees B, and employees C employees have a high or dangerous risk, and urgent repairs are needed. The cause of the high risk experienced is caused by the inadequate use of facilities, the need to update work facilities according to ergonomic standards in the world of work, and the holding of good and correct computer office ergonomics training to reduce injuries when using computers.